Evaluation of Carbazole Degradation by Enterobacter sp. Isolated from Hydrocarbon Contaminated Soil - Sanjay Gupta, Nidhi Gupta*, Gajendra B Singh, Sudha Srivastava (Recent Research in Science and Technology, 2011)
A gram-negative bacterium designated A8 was isolated from hydrocarbon contaminated soil collected from petrol pump of Ahmedabad, India. Its ability to degrade carbazole, nitrogen containing polycyclic aromatic hydrocarbon was checked in basal salt media containing 3 mM of carbazole. Growing cells of the isolate could degrade 83% of carbazole in 240 hours. On the basis of different biochemical and physiological tests, isolate A8 was identified as Enterobacter sp. To the best of my knowledge this is the first report on degradation of carbazole by Enterobacter sp.